THE PRESERVATION OF BATIK THROUGH TECHNOLOGY: THE ROLE OF BATIK FRACTAL AND JBATIK SOFTWARE - Adiyanti, Putu Ayu (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Batik Fractal is an innovation that integrates traditional Batik art with modern technology through the application of fractal mathematical formulas to create more complex and innovative Batik designs. This technology developed through jBatik software, allows for a more efficient design and production process without compromising the aesthetic and philosophical value of batik as a cultural heritage. This research aims to examine the application of fractal technology in Batik design, as well as its impact on the preservation of batik art, production efficiency, and batik competitiveness in the global market. A descriptive qualitative research approach is used to collect data through observation and analysis of documents then analyzed to provide a comprehensive understanding of the development of Batik Fractal. The results of this study show that Batik Fractal provides a new dimension in Batik design while strengthening the relevance of Batik in the modern era and the international market.